THE EFFECT OF ITO, CR, DER, TATO AND WCTO ON ROE IN VARIOUS INDUSTRIAL COMPANIES LISTED ON THE IDX - Jessica Jessica; Wirda Lilia; Cherlyn Leonardy; Meiluawaty Kartika; Nehemia Panggabean (Berkala Akuntansi dan Keuangan Indonesia, 2019)
This study aims to analyze the effect of inventory turnover, current ratio, debt to equity ratio, total assets turnover, and working capital turnover on return on equity in various industrial companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach method. The population in this study are all various industrial companies listed on the Indonesia Stock Exchange for the period 2014-2017. The sampling technique used is purposive sampling with 64 companies as samples. This study uses secondary data taken from the Indonesia Stock Exchange. This study was analyzed using multiple linear regression analysis. The coefficient of determination of return on equity is 42.8% which is influenced by inventory turnover, current ratio, debt to equity ratio, total assets turnover, and working capital turnover. The results showed that inventory turnover, current ratio, debt to equity ratio, total assets turnover, and working capital turnover simultaneously had an effect on return on equity. Partially, inventory turnover, current ratio, and working capital turnover have no effect on return on equity, debt to equity ratio has a negative and significant effect on return on equity, and total assets turnover has a positive and significant effect on return on equity.